Optimising technical skills and physical loading in small-sided basketball games - Klusemann, M. J.; Pyne, D. B.; Foster, C.; Drinkwater, E. J. (17th Annual Congress of the European College of Sport Science (ECSS), Bruges, 4. -7. July 2012, 2012)
The organisational pattern of small-sided basketball games defines the balance between physical and physiological demands and technical practice needed for competitive success. Differences in technical, physiological and physical demands of small-sided basketball games related to the number of players, court size and work-to-rest ratios are not well characterised. Methods: A controlled trial was conducted to compare the influence of number of players (2v2 / 4v4), court size (half / full court) and work-to-rest ratios (2x5 min / 4x2.5 min) on the demands of small-sided games. Sixteen elite male and female junior players (aged 15-19 years) completed eight variations (2 x 2 x 2) of a small-sided game in randomised order over a six week period. Technical elements (e.g. shots, rebounds and passes)and movement patterns were assessed by video analysis. Heart rate responses and rating of perceived exertion (RPE) were measured to assess the physiological load. Results: There were ~60% more technical elements in 2v2 than 4v4 and ~20% more in half court than full court games. Heart rate (86 ± 4% v 83 ± 5% of maximum; mean ± SD) and RPE (8 ± 2 v 6 ± 2; scale 1-10) were moderately higher in 2v2 than 4v4 small-sided games. The 2v2 format elicited substantially more sprints (36 ±12%; mean ±90% confidence limits) and high intensity shuffling (75 ±17%) than 4v4. Full court games required substantially more jogging (9 ±6%) than half court games. Discussion: This is the first study to systematically investigate the effect of the number of players, court size and work-to-rest ratios on the various demands of small-sided basketball games. The main finding is that the number of players has the largest influence on the technical, physiological and high intensity movement patterns in small-sided basketball games. Court size and work-to-rest ratios can influence the frequency of various movement patterns. Basketball coaches can manipulate different variables of basketball drills and small-sided games to vary the technical, physiological and physical demands of their basketball practice. Applying these training concepts will help coaching staff meet specific training and conditioning goals.